Síntese e caracterização de copolímeros do tipo doador-aceitador contendo benzotiadiazol e dicetopirrolopirrol - Oliveira, Pollyana Aparecida Almeida de (2025)
Conjugated polymers have been breaking the paradigm that polymers serve only as insulators. They have been the subject of intense scientific research in recent years due to their ability to act as semiconductors, with easy film arrangement, flexibility, and other characteristics that allow them to complement and even replace some optoelectronic devices. In this sense, homopolymers are not as attractive because they have high bandgap energy, limiting light absorption. However, copolymers with electron-donating units such as fluorene derivatives and electron-accepting units such as benzothiadiazole (BT) and diketopyrrolopyrrole (DPP) are being increasingly studied, as they allow modification of the HOMO/LUMO energy levels, increasing charge carrier mobility and decreasing the bandgap energy, which improves photon absorption4essential characteristics for their application in optoelectronics. From this perspective, the objective of this research was the synthesis and characterization of D-A-D-A copolymers with fluorene, diketopyrrolopyrrole, and benzothiadiazole, investigating how their proportions affect the materials’ properties and technological applications. The structural, optical, and electronic properties of these copolymers were investigated using Nuclear Magnetic Resonance, Ultraviolet-Visible spectroscopy, and fluorescence emission spectrophotometry. Initial findings also indicate that these polyfluorene derivatives can be used as fluorescence chemosensors for iron and chromium cations.